Primary Grynfeltt's hernia combined with intermuscular lipoma: A case report. (July 2021) - Heo, Tae Gil
Abstract: Introduction: Grynfeltt's hernia (superior lumbar hernia) is a rare posterolateral abdominal wall defect and is often misdiagnosed as an abdominal wall lipoma. I recently experienced a case of primary Grynfeltt's hernia combined with intermuscular lipoma that was managed surgically. Presentation of case: A 79-year-old man presented with a left flank mass. In the seated position, when the abdominal pressure was raised by deep breathing after left flank extension, the mass became clearer. Abdominal computed tomography (CT) findings showed herniated perirenal fat via the superior lumbar triangle and a surrounding intermuscular lipoma. After intermuscular lipoma removal, the hernia defect was closed with primary simple interrupted sutures. Currently, at 5 months postoperatively, no recurrence has been observed. Discussion: On physical examination of Grynfeltt's hernia, it may be difficult to identify the distinct mass because of the relatively large overlaying of the latissimus dorsi muscle. Thus, Grynfeltt's hernia can be misdiagnosed as soft tissue tumors, such as lipomas. Abdominal CT findings may provide an accurate diagnosis and reveal the anatomical structures and additional lesions. Proper surgical treatment should be planned based on the etiology, size of the hernia defect, condition of the surrounding structures, and presence of additional lesions. Conclusion: Grynfeltt's hernia should be considered when a mass is palpable on the posterolateral abdominal wall and in cases where the size of the mass changes when changing position. CT examination of the abdomen may help make an accurate diagnosis, observe additional lesions, and develop a surgical-treatment plan. Highlights: Grynfeltt's hernia could be misdiagnosed as an abdominal wall lipoma. A 79-year-old man presented with a left flank mass. Abdominal CT showed herniated perirenal fat via the superior lumbar triangle. A surrounding lipoma was noted. The hernia defect was closed with primary simple interrupted sutures.